Numerical analysis of corrugated steel plate bridge with reinforced concrete relieving slab - Beben, Damian; Stryczek, Adam (Journal of Civil Engineering and Management, 2016)
The paper presents a numerical analysis of corrugated steel plate (CSP) bridge with reinforced concrete (RC) relieving slab under static loads. Calculations were made based on the finite element method using Abaqus software. Two computation models were used; in the first one, RC slab was used, and the other was without it. The effect of RC slab to deformations of CSP shell was determined. Comparing the computational results from two numerical models, it can be concluded that when the relieving slab is applied, substantial reductions in displacements, stresses, bending moments and axial thrusts are achieved. Relative reductions of displacements were in the range of 53–66%, and stresses of 73–82%. Maximum displacements and bending moments were obtained at the shell crown, and maximum stresses and axial thrusts at the quarter points. The calculation results were also compared to the values from experimental tests. The course of computed displacements and stresses is similar to those obtained from experimental tests, although the absolute values were generally higher than the measured ones. Results of numerical analyses can be useful for bridge engineering, with particular regard to bridges and culverts made from corrugated steel plates for the range of necessity of using additional relieving elements.First published online: 15 Jan 2015